Fabrication and Characterization of Fiber-Reinforced Composite Sandwich Structures Obtained by Fused Filament Fabrication Process - BUICAN, George Răzvan; ZAHARIA, Sebastian‑Marian; POP, Mihai Alin; CHICOȘ, Lucia‑Antoneta; LANCEA, Camil; STAMATE, Valentin‑Marian; PASCARIU, Ionuț Stelian (MDPI, 2021)
The application of fused filament fabrication processes is rapidly expanding in many domains such as aerospace, automotive, medical, and energy, mainly due to the flexibility of manufacturing structures with complex geometries in a short time. To improve the mechanical properties of lightweight sandwich structures, the polymer matrix can be strengthened with different materials, such as carbon fibers and glass fibers. In this study, fiber-reinforced composite sandwich structures were fabricated by FFF process and their mechanical properties were characterized. In order to conduct the mechanical tests for three-point bending, tensile strength, and impact behavior, two types of skins were produced from chopped carbon-fiber-reinforced skin using a core reinforced with chopped glass fiber at three infill densities of 100%, 60%, and 20%. Using microscopic analysis, the behavior of the breaking surfaces and the most common defects on fiber-reinforced composite sandwich structures were analyzed. The results of the mechanical tests indicated a significant influence of the filling density in the case of the three-point bending and impact tests. In contrast, the filling density does not decisively influence the structural performance of tensile tests of the fiber-reinforced composite sandwich structures. Composite sandwich structures, manufactured by fused filament fabrication process, were analyzed in terms of strength-to-mass ratio. Finite element analysis of the composite sandwich structures was performed to analyze the bending and tensile behavior.
This paper was published open access in Coatings (Vol. 11, Issue 5, Article 601) under the CC BY 4.0 license on 19 May 2021. DOI: 10.3390/coatings11050601.
Keywords: fused filament fabrication; fiber-reinforced composite sandwich structures; infill density; mechanical proprieties; finite element analysis